MPA Modulates Tight Junctions' Permeability via Midkine/PI3K Pathway in Caco-2 Cells: A Possible Mechanism of Leak-Flux Diarrhea in Organ Transplanted Patients - Khan, Niamat; Binder, Lutz; Pantakani, D. V. Krishna; Asif, Abdul R. (Frontiers in Physiology, 2017)
Mycophenolic acid (MPA) is prescribed to prevent allograft rejection in organ transplanted patients. However, its use is sporadically linked to leak flux diarrhea and other gastrointestinal (GI) disturbances in around 75% of patients through yet unknown mechanism. Recently, we identified Midkine as a modulator of tight junctions (TJs) permeability in MPA treated Caco-2 monolayer. In the present study, we investigated the possible involvement of Midkine dependent PI3K pathway in alteration of TJs under MPA treatment. Caco-2 cells were grown as monolayer to develop TJs and were treated for 72 hours with DMSO (control) or MPA in presence and absence of Midkine inhibitor (iMDK) or PI3K inhibitors (LY/AMG). Caco-2 monolayer integrity was assessed by transepithelial electrical resistance (TEER) and FITC-dextran assays. Our functional assays showed that PI3K inhibitors (LY/AMG) can significantly inhibit the compromised TJs integrity of MPA-treated Caco-2 cells monolayer. Chromatin immunoprecipitation analyses showed a significant epigenetic activation of Midkine, PI3K, Cdx-2, and Cldn-2 genes and epigenetic repression of Cldn-1 gene after MPA treatment. The MPA-induced epigenetic alterations were further confirmed by mRNA and protein expression analysis. Collectively, our data show that PI3K pathway as the downstream target of Midkine which in turn modulates p38MAPK and pAKT signaling to alter TJs permeability in Caco-2 cell monolayers treated with MPA. These results highlight the possible use of either Midkine or PI3K inhibitors as therapeutic agents to prevent MPA induced GI disturbances.